1985
DOI: 10.1007/bf00034590
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour of silver carp Hypophthalmichthys molitrix Val. and its impact on the food web in Lake Kinneret, Israel

Abstract: Silver carp Hypophtha/michthvs molitrix

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 14 publications
5
72
0
1
Order By: Relevance
“…This suggests a diet overlap among native planktivores (e.g., the fingerlings of all other fish species) and bigheaded carps, which may lead to a strong interspecific competition and probably to reduced fitness in native fish populations in such a nutrient poor lake. Based on our results, we suggest and urge a more effective and targeted bigheaded carp removal from Lake Balaton to eliminate a considerable ecological risk because the presence of these exotic species could result in the decline of native fish populations, as previous studies have demonstrated (Spataru and Gophen, 1985;Chick and Pegg, 2001;Sampson et al, 2009). …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This suggests a diet overlap among native planktivores (e.g., the fingerlings of all other fish species) and bigheaded carps, which may lead to a strong interspecific competition and probably to reduced fitness in native fish populations in such a nutrient poor lake. Based on our results, we suggest and urge a more effective and targeted bigheaded carp removal from Lake Balaton to eliminate a considerable ecological risk because the presence of these exotic species could result in the decline of native fish populations, as previous studies have demonstrated (Spataru and Gophen, 1985;Chick and Pegg, 2001;Sampson et al, 2009). …”
Section: Discussionmentioning
confidence: 57%
“…Most studies cite silver carp as primarily phytoplankton feeder, able to collect algae larger than 10 µm (Sieburth et al, 1978;Hampl et al, 1983;Smith, 1989;Vörös et al, 1997), while others suggest that silver carp is able to collect even nanoplankton (<10 µm) (Cremer and Smitherman, 1980;Xie, 1999;Görgényi et al, 2015). However, Spataru and Gophen (1985) revealed that the proportion of zooplankton in the diet of silver carps can be up to 50% in some cases, and several other studies have demonstrated that the presence of silver carp results in a zooplankton community dominated by smaller individuals (e.g., Fukushima et al, 1999;Lu et al, 2002). In this study, our aim was to explore the feeding habits of bigheaded carps in Lake Balaton, where the stock consists mainly of hybrid individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of silver carp feeding have suggested that they filter-feed on phytoplankton. This is the main reason why silver carp have been heavily stocked to reduce algal abundance in eutrophic lakes in southern China However, recent studies showed that silver carp are able to filter both phytopiankton and cladoceran species (Spataru andGophen 1985, Dong andLi 1994). Although we did not analyze diets of silver carp, our results indicated that abundant silver carp could suppress populations of large-bodied Daphnia sp..…”
Section: Junementioning
confidence: 61%
“…Silver carp gill rakers also have a sponge-like filtering apparatus with small pores about 100 μm in diameter (Boulenger, 1901;Fang, 1928). The ability of both these species to capture tiny phytoplankton and zooplankton efficiently is well known, leading them to being used to clean up eutrophic bodies of water (Smith, 1985;Spataru and Gophen, 1985;Smith, 1989;Kolar et al, 2005) and giving them some of the highest growth rates noted for any fish (Abdelghany and Ahmad, 2002). It is generally assumed, but unproven, that their ability to feed on tiny particles is attributable to their EO which also produces copious amounts of mucus and has often been found to contain boli of food mixed with mucus (Wilamovski, 1972;Spataru and Gophen, 1985;Kolar et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of both these species to capture tiny phytoplankton and zooplankton efficiently is well known, leading them to being used to clean up eutrophic bodies of water (Smith, 1985;Spataru and Gophen, 1985;Smith, 1989;Kolar et al, 2005) and giving them some of the highest growth rates noted for any fish (Abdelghany and Ahmad, 2002). It is generally assumed, but unproven, that their ability to feed on tiny particles is attributable to their EO which also produces copious amounts of mucus and has often been found to contain boli of food mixed with mucus (Wilamovski, 1972;Spataru and Gophen, 1985;Kolar et al, 2005). The bigheaded carps feed using buccal pumping (active ingestion of water though their gills by opercular flaring) (Dong and Li, 1994), but how that might be connected to food identification, filtration and EO function is unknown.…”
Section: Introductionmentioning
confidence: 99%